Long term portfolio construction - Musilika, Oskar (Department of Finance and Tax, 2016)
Financial analyst commonly advice individual investors with a long investment horizon to invest in portfolios comprised more of equities. This advice is usually coupled with the practice of shifting the investor's portfolio from risky asset holdings towards bonds and cash as the investor's target date gets closer. This view rests on the notion that equities tend to be less risky over the long horizon and that stock returns exhibit mean reversion overtime. The purpose of this dissertation is to find the optimal asset allocation over various investment horizons; and investigate how the optimal asset allocation changes over the long investment horizon. The study uses data from South Africa's financial market covering the period December 2001 to December 2014. The mean - variance framework generated the optimal asset allocation over 12 investment horizons. The study finds that, over 90 percent of the portfolio should be vested into fixed - income South African bonds, with little over 5 percent equities allocation, over longer investment periods. In addition, the study found evidence of time diversification on the JSE all shares index and the presence of mean reversion properties for the all s hares index. With these conclusions, implications and recommendations are suggested